Menggali Tantangan Pada Pelaku Usaha Kecil Menengah Dalam Menerapkan SAK-EMKM (Studi Kasus Pada UMKM Putikasari Rottan Gresik) - Binti Habibah; Nufaisa Nufaisa; Ratna Anggraini Aripratiwi; selvia eka aristantia (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
With the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM), it is easier for MSME players to provide information that can be used as a basis for various activities, such as running a business, determining prices, meeting tax requirements, and so on. In fact, Putikasari Rottan MSMEs still use simple records consisting of income and expenses. The aim of this research is to gain an understanding of the challenges faced by Putikasari Rottan MSMEs in implementing SAK EMKM. This research uses a qualitative approach with a case study type of research. The informants in this research were 3 people, namely the owner and the employees of UMKM Putikasari Rottan. This research uses primary data sources and secondary data, and uses interview and observation techniques in data collection. The results of this research show that the challenges for UMKM Putikasari Rottan in implementing SAK EMKM are as follows: 1) According to UMKM Putikasari Rottan, accounting is complicated 2) Lack of understanding when managing finances 3) Educational factors 4) Lack of human resources who have knowledge of SAK EMKM 5) Uncertainty of profits obtained. And 6) SAK EMKM Accounting Socialization and Training Has Not Been Done in MSMEs. This research provides recommendations to MSME players to explore information regarding SAK EMKM to improve the quality of their business financial reports. Keywords: SAK EMKM, financial accounting, MSMEs